(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Several years ago, a volunteer project study team prepared a concept level Technical Report on the Multi-Purpose Melamchi Project (the MPMP, by Dan Jantzen, Bikash Pandey, Ratna Sansar Shrestha and Odd Hoftun, 2008). The ongoing Melamchi Project is single purpose project, to provide drinking water for the Kathmandu Valley. The Study Team wrote that the present Melamchi Project scope is limited and that its full potential should be harnessed by making it multi-purpose so that the more benefits are accrued to the people of Melamchi-Bagmati corridor. The MPMP authors propose a wide range of initiatives in hydropower generation, and making available additional water for irrigation in the Bagmati Irrigation Project. The cost estimates were prepared by Sanima Hydro and Engineering (P.) Ltd.; the Preliminary Environmental Assessment was undertaken by Dr. Toran Sharma; and the Irrigation Analysis was by Dilip Karki. Furthermore, the study team has proposed to implement the MPMP as a Public-Private Partnership, where the hydropower component is taken by the private sector. In addition to the 26km Melamchi-Sundarijal tunnel, other long additional tunnels are proposed in the Himalayan Geology. These ideas and proposals need to be further discussed for the benefits and risks, alike. The following is the Executive Summary of the MPMP report. The four figures presented are self-explanatory. DOI: http://dx.doi.org/10.3126/hn.v9i0.7070 Hydro Nepal Vol.9 July 2011 35-37